Analisis Dampak Liberalisasi Perdagangan terhadap Usaha Mikro, Kecil, dan Menengah (UMKM) di Indonesia - Muhammad Tsani Aththoriq; Anis Supriyatin; Sirfi Nur Fitriani; Sarpini Sarpini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Trade liberalization has become an integral part of economic globalization, providing both opportunities and challenges for the Micro, Small, and Medium Enterprises (MSMEs) sector in Indonesia. This study aims to analyze the impact of trade liberalization on MSMEs, including the opportunities it creates, the challenges faced, and the adaptive strategies that can be implemented. Using a qualitative approach based on literature reviews, this study explores various references related to the socio-economic impacts and policy implications for the MSME sector. The findings indicate that although trade liberalization opens broader market access and enhances innovation potential, MSMEs face significant challenges such as global competition, limited capital, and compliance with international quality standards. Therefore, inclusive policies and empowerment programs are essential to ensure MSMEs’ sustainability and equitable benefits from trade liberalization.